2014
DOI: 10.3171/2014.6.jns132577
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of erythropoietin in treating experimental traumatic brain injury: a systematic review of controlled trials in animal models

Abstract: S yStematic reviews and meta-analyses are fundamental tools used to interpret the effectiveness of a treatment across many studies. Recently, the need to conduct systematic reviews and meta-analyses of animal studies modeling clinically relevant problems has been highlighted. 9,13,36 In particular, systematic reviews of animal experiments will allow decisions regarding the design and conduct of subsequent clinical trials to be based on the entirety of the existing evidence that is synthesized in an unbiased ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 54 publications
(100 reference statements)
5
40
0
Order By: Relevance
“…In agreement with TBI studies, we detected less cell death, optic nerve degeneration, glial reactivity, and oxidative stress by systemic injection of EPO (for review see 39 ). Further, as in other models, we also detected efficacy with EPO when treatment was delayed until 24h post-injury.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with TBI studies, we detected less cell death, optic nerve degeneration, glial reactivity, and oxidative stress by systemic injection of EPO (for review see 39 ). Further, as in other models, we also detected efficacy with EPO when treatment was delayed until 24h post-injury.…”
Section: Discussionsupporting
confidence: 89%
“…Erythropoietin has multiple mechanisms of action that can be beneficial for treating TBI, 14,69,90 including enhancing the survival and maturation of oligodendrocytes and neurons after injury. 38,53,97 Similar to the effect on erythroblasts in the bone marrow, unbound EPO receptors (EPORs) promote neural cell apoptosis.…”
mentioning
confidence: 99%
“…Administering EPO and maintaining hemoglobin >10 g/dL in patients with TBI did not result in neurobehavioral improvement, but neurological improvement occurred after 6 months41). Peng et al reported that EPO helped to treat experimental TBI by reducing lesion volume and improving neurological outcome39).…”
Section: Discussionmentioning
confidence: 99%